Immuno-oncology in GI tumours: Clinical evidence and emerging trials of PD-1/PD-L1 antagonists. (October 2018) - Stein, Alexander; Moehler, Markus; Trojan, Jörg; Goekkurt, Eray; Vogel, Arndt
Abstract: The use of immune checkpoint inhibitors constitutes an emerging therapeutic field for the therapy of gastrointestinal (GI) malignancies following the recent FDA approvals of PD-1 inhibitors for esophago-gastric adenocarcinoma, hepatocellular carcinoma and for microsatellite-instable tumors, which are mainly colorectal cancers. This paper reviews the clinical evidence end of 2017 and discusses the clinical development programs of atezolizumab, avelumab, durvalumab, nivolumab and pembrolizumab in GI-tract cancers. Since 2014, these antagonists of the PD-1/PD-L1 axis have gained approval for use in numerous other tumors. Phase II trials and phase I expansion cohorts demonstrate clinical activity in patients with oesophageal, gastric, colorectal, anal and hepatic cancer. Signals of outstanding efficacy are particularly observed in biomarker selected populations and for certain combination regimen. Comprehensive phase III development programs have been initiated in oesophageal and gastric cancer, with randomized trials ongoing in hepatocellular and colorectal cancer as well.